Diketopyrrolopyrrole‐Based and Tetracyano‐Bridged Small Molecules for Bulk Heterojunction Organic Solar Cells. Issue 3 (5th January 2018) - Patil, Yuvraj; Misra, Rajneesh
Abstract: Research on bulk heterojunction organic solar cells has rapidly grown over the past two decades, and device performance has reached power conversion efficiencies over 13 %. In this focus review, we highlight design strategies used for the development of diketopyrrolopyrrole‐ and tetracyano‐based molecular donors. We also describe how tetracyano‐bridged non‐fullerene acceptors can be developed by a click‐type [2+2]‐cycloaddition–electrocyclic ring‐opening reaction of acetylene‐bridged small molecules with tetracyanoethylene by simple modification. Abstract : Bridging the gaps : Design strategies for the development of diketopyrrolopyrrole (DPP)‐based and tetracyano‐bridged molecular architectures are highlighted. Important structural changes in donors and acceptors and their impact on device performance are also discussed. Tetracyanobutadiene‐bridged small molecules are also explored as acceptors for bulk heterojunction organic solar cells.